Dynamics of endothelial function in patients with arterial hypertension with different cardiovascular risk against the background of antihypertensive therapy - N.O. Pertseva; T.S. Turlyun; N.A. Sanina (Medičnì Perspektivi)
The aim of the work was to investigate the dynamics of endothelial markers in patients with arterial hypertension with different cardiovascular risk under the influence of the prescribed treatment during a year of observation. The first group (with a moderate risk of cardiovascular events) included 48 patients with arterial hypertension (AH). The second group consisted of 54 patients with hypertension and a high risk of cardiovascular events, namely type 2 diabetes. Each group of patients was randomized into two subgroups by blood pressure (BP) medication. In patients of subgroup 1a (n=29) and subgroup 2a (n=35) – the main subgroups – the therapy necessarily included the angiotensin II receptor antagonist losartan potassium in a dosage of 50-150 mg/day, depending on the blood pressure level. Patients of subgroup 1b (n=19) and subgroup 2b (n=19) – comparison subgroups were treated with antihypertensive drugs of other first-line groups according to the data of the unified clinical protocol for the treatment of hypertension. According to the ROC analysis, it was determined that the dynamics of endothelin-1 (ET-1) indicators after 9 and 12 months of therapy (a decrease of 12% or more from the initial level) can predict the normalization of indicators of the coagulation and anticoagulation systems with indicators of sensitivity and specificity – 85% (95% CI 62.1-96.6%) and 92.9% (95% CI 76.5-98.9%), respectively. A decrease in the level of Willebrand factor (fV) by 23% or more due to such a treatment time can be used as a prognostic sign in determining the regression of endothelial dysfunction with sensitivity – 75% (95% CI 50.9-91.2%), specificity – 100% (95% CI 87.5-100%). According to the given data, both in the group with moderate and with high cardiovascular risk, there is a relationship between endothelial dysfunction (ED) and the duration of hypertension, indicators of the lipid spectrum and abdominal obesity – factors that increase the viscous resistance of the blood circulation, as well as platelet hyperactivity in the bloodstream. We have also established that according to the dynamics of ET-1 indicators after 9 and 12 months of therapy (decrease by 27% or more from the initial level), it is possible to predict the normalization of indicators of the coagulation and anticoagulation systems with indicators of sensitivity – 81.8% (95% CI 59.7-94.7%), specificity – 90.6% (95% CI 75-97.9%). A decrease in the level of fV by 24.5% or more after a year of treatment can be used as a prognostic sign in determining the regression of endothelial dysfunction with sensitivity – 68.2% (95% CI 45.1-86.1%), specificity – 71.9% (95% CI 53.3-86.2%). The obtained results testify to the dominant role of type 2 diabetes as a factor in platelet disorders of hemostasis. Taking into account the positive dynamics of the above-mentioned markers of ED during the year of treatment, their relationship with the reduction of blood pressure, indicators of the lipid spectrum and abdominal obesity, it should be noted the positive effect of angiotensin II receptor blockers (BRA II) as endothelioprotective drugs. Considering the irrefutable literary data about the absence of thrombomodulin in the blood stream, even its insignificant appearance indicates the presence of endothelial dysfunction. Determining the state and dynamics of changes in endothelial function under the influence of prescribed therapy will make it possible to improve the diagnosis of endothelial function disorders and increase the effectiveness of treatment of patients with hypertension and various cardiovascular risks.